2013
DOI: 10.1007/s00264-012-1765-5
|View full text |Cite
|
Sign up to set email alerts
|

Total knee arthroplasty after high tibial osteotomy: a comparison of opening and closing wedge osteotomy

Abstract: Purpose High tibial osteotomy (HTO) is frequently used to treat varus osteoarthritis in younger patients with the goal of delaying the need for total knee arthroplasty (TKA). While it has been reported that the results of TKA following HTO are worse than those in patients without prior knee surgery, the influence of osteotomy technique (medial openingwedge versus lateral closing-wedge) has not been explored. The purpose of this study was to evaluate the influence of HTO technique on the performance and results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 26 publications
1
53
0
5
Order By: Relevance
“…Three outcomes of RCTs were different from all studies, which may be related to the sample size or other factors. Second, the follow-up period was diverse, most studies were < 2 years, two studies 14,30 were > 5 years, and partial results were different from previous studies. Bastos Filho et al 30 found that the patellar height (BPI) of OWO was not statistically different from that of CWO.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Three outcomes of RCTs were different from all studies, which may be related to the sample size or other factors. Second, the follow-up period was diverse, most studies were < 2 years, two studies 14,30 were > 5 years, and partial results were different from previous studies. Bastos Filho et al 30 found that the patellar height (BPI) of OWO was not statistically different from that of CWO.…”
Section: Discussionmentioning
confidence: 95%
“…Second, the follow-up period was diverse, most studies were < 2 years, two studies 14,30 were > 5 years, and partial results were different from previous studies. Bastos Filho et al 30 found that the patellar height (BPI) of OWO was not statistically different from that of CWO. van Egmond et al 14 found that the clinical results of CWO were better than those of OWO, according to the VAS satisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies [8,11,19] reported that the femorotibial angle after TKA following HTO did not significantly differ from that after primary TKA. Furthermore, some studies found that the patellar height was altered after HTO [6,28]. Bae et al [10] and Efe et al [13] reported that the IS ratio did not significantly differ between the RHTO and PTKA groups; however, Kazakos et al [18] reported the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Conversion TKA after HTO may be more technically demanding than primary TKA due to the difficulty of the surgical approach, the ligamentous imbalance, and the anatomical distortion of the proximal tibial metaphysis [17,37]. Bastos et al [28] reported that incidence of additional procedures were required for the surgical approach because of the difficult patellar eversion in conversion TKA after HTO. Nagamine et al [38] reported that a tibial offset stem may be required to solve the problem of translational and meta-diaphyseal mismatch of the tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in this study, stemmed implants were used in 17% of the revised UKAs and in just 4% of the revised Htos. Bastos Filho et al (47) found an increased need for tibial tubercle osteotomy in tKA after CWHto and for medial release in patients previously submitted to oWHto.…”
Section: Conversion To Total Knee Arthroplasty (Tka)mentioning
confidence: 98%